2016
DOI: 10.1101/cshperspect.a029231
|View full text |Cite
|
Sign up to set email alerts
|

Voltage-Gated Potassium Channels: A Structural Examination of Selectivity and Gating

Abstract: Voltage-gated potassium channels play a fundamental role in the generation and propagation of the action potential. The discovery of these channels began with predictions made by early pioneers, and has culminated in their extensive functional and structural characterization by electrophysiological, spectroscopic, and crystallographic studies. With the aid of a variety of crystal structures of these channels, a highly detailed picture emerges of how the voltage-sensing domain reports changes in the membrane el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
89
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(89 citation statements)
references
References 154 publications
(194 reference statements)
0
89
0
Order By: Relevance
“…KcsA is a K + channel from the bacterium Streptomyces lividans with no explicit VSD 94,95 . Given its similarities to eukaryotic inwardly rectifying K + channels and the pore domain of K V channels, the structure and activity of KcsA has been intensely studied in the past 2 decades as a model protein for permeation and C-type or “slow” inactivation in ion channels 96 . The activity of KcsA is controlled by hydrogen ions; fast decrease of the pH in the intracellular side activates the channels.…”
Section: Introductionmentioning
confidence: 99%
“…KcsA is a K + channel from the bacterium Streptomyces lividans with no explicit VSD 94,95 . Given its similarities to eukaryotic inwardly rectifying K + channels and the pore domain of K V channels, the structure and activity of KcsA has been intensely studied in the past 2 decades as a model protein for permeation and C-type or “slow” inactivation in ion channels 96 . The activity of KcsA is controlled by hydrogen ions; fast decrease of the pH in the intracellular side activates the channels.…”
Section: Introductionmentioning
confidence: 99%
“…7). Therefore, these results suggest that changes of the membrane potential are sensed by the S4 translocation that are 12 Å at the largest, leading to the allosteric regulation of the gating at the PD229.…”
Section: Discussionmentioning
confidence: 81%
“…A combination of molecular dynamics simulations and electrophysiology suggested that conformational changes at the cytosolic end of the pore act to remove steric restraints at the selectivity filter, producing structural fluctuations. These may reduce K + affinity and increase ion permeation, leading to a conducting (open) state; after opening, however, these movements may be coupled to further structural changes at the selectivity filter that block permeation, leading to an inactivated state (Figure 2B) [185188]. These observations are consistent with combined electrophysiological and computational studies in MthK, which show that reduction in extracellular K + can lead to K + dissociation, followed by structural changes in the selectivity filter to a non-conducting state [108, 164].…”
Section: Key Questions Subject To Interdisciplinary Study In Ion Tmentioning
confidence: 99%